Employing a Quality Improvement Database to Observe the Gaps in Care at a Student-Run Free Clinic - Jessica Grimmond; Melanie Menning (Journal of Student-Run Clinics, 2022)
The Student Health Alliance Reaching Indigent Needy Groups (SHARING) clinics are student run freeclinics (SRFCs) at the University of Nebraska Medical Center that serve low income, uninsured adultsin Omaha, Nebraska. Like many other SRFCs, they face multiple barriers to providing high quality care.To address this, the SHARING Quality Improvement (QI) Database was created. QI has many definitions,but, overall, it is a method of analyzing clinic performance and the changes made to improvethe clinic. Before this database, there was no way of continuously tracking clinic metrics over time, soprevious QI projects required timely data abstraction that often only evaluated retrospective outcomeswith limited real-time data to track clinical outcomes as changes were implemented therebylimiting our ability to implement further changes to improve patient health. A review of SRFC literaturereveals a lack of a model or guide on how to assess quality of care in SRFCs and track patient dataover time. This study seeks to fill this gap. Our database consists of a patient list of electronic medicalrecords that were compiled in the charting system Epic. The patient data is exported into a MicrosoftExcel document each month and clinic metrics are analyzed, thus providing a real-time dashboard ofquality metrics for the clinic. This database will be utilized to inform decisions regarding the reform ofclinic processes. This database model can be used at other SRFCs to monitor quality of care providedat their clinics and implement QI measures accordingly.